Rheumatic Heart Disease in Pregnancy: New Strategies for an Old Disease? - Geraldine Vaughan; Angela Dawson; Michael Peek; Karen Sliwa; Jonathan Carapetis; Vicki Wade; Elizabeth Sullivan (Ubiquity Press, 2021)
RHD in pregnancy (RHD-P) is associated with an increased burden of maternal and perinatal morbidity and mortality. A sequellae of rheumatic fever resulting in heart valve damage if untreated, RHD is twice as common in women. In providing an historical overview, this commentary provides context for prevention and treatment in the 21 st century. Four underlying themes inform much of the literature on RHD-P: its association with inequities; often-complex care requirements; demands for integrated care models, and a life-course approach. While there have been some gains particularly in awareness, strengthened policies and funding strategies are required to sustain improvements in the RHD landscape and consequently improve outcomes. As the principal heart disease seen in pregnant women in endemic regions, it is unlikely that the Sustainable Development Goal 3 target of reduced global maternal mortality ratio can be met by 2030 if RHD is not better addressed for women and girls.